Paradigm of Religious Moderation in Curriculum Design for Islamic Religious Education at State Islamic Senior High School of Bangka Belitung - Suparta, Suparta; Wahyudi, Wahyudi (Madania: Jurnal Kajian Keislaman, 2024)
The results of several observations regarding the religious tolerance attitudes of students in Bangka Belitung are pretty worrying, even though some tend to be radical. This research explores the paradigm of religious moderation in the Islamic religious education curriculum at Madrasah Aliyah Negeri Bangka Belitung. This research explores qualitatively the application of religious moderation in the curriculum of Islamic religious education material. Research data was taken from the MAN Pangkal Pinang and MAN 1 Muntok curriculum documents. Researchers also surveyed by distributing questionnaires to 346 students from the two schools. The research results show that the content of religious moderation has been integrated into the Islamic religious education curriculum, both in Jurisprudence, History of Islamic Culture, Al-Qur'an Hadith, and Aqidah Akhlak. However, the tendency towards a radical and robust understanding of Islam is still strong. It is evident from the survey results, namely 55.4% of respondents from MAN Pangkal Pinang and 53% of respondents from MAN 1 Muntok stated that adhering to the Pancasila ideology is more important. Almost half of the students do not agree that Pancasila should be made the state ideology. This phenomenon must receive serious attention from the government so that they comply with the laws and regulations of the Republic of Indonesia. Hasil beberapa pengamatan terhadap sikap toleransi beragama para siswa di Bangka Belitung cukup memprihatinkan, bahkan di antaranya cenderung radikal. Penelitian ini bertujuan untuk mengeksplorasi paradigma moderasi beragama dalam kurikulum pendidikan agama Islam di Madrasah Aliyah Negeri Bangka Belitung. Penelitian ini mencoba menelusuri secara kualitatif penerapan moderasi beragama dalam kurikulum materi pendidikan gama Islam. Data penelitian diambil dari dokumen kurikulum MAN Pangkal Pinang dan MAN 1 Muntok.  Selain itu, peneliti juga melakukan survey dengan menyebarkan angket terhadap 281 siswa dari kedua sekolah tersebut. Hasil penelitian menyebutkan bahwa muatan moderasi beragama sebenarnya telah diterapkan secara terintegrasi dalam kurikulum pendidikan agama Islam, baik dalam mata Pelajaran Fikih, Sejarah Kebudayaan Islam, Al-Qur’an Hadis, maupun Akidah Akhlak. Akan tetapi, kecenderungan terhadap pemahaman Islam secara radikal dan kuat masih kuat. Hal ini terbukti dari hasil survey, yakni 55, 4% responden dari MAN Pangkal Pinang dan 53% responden dari MAN 1 Muntok menyatakan bahwa berpegang teguh ideologi Pancasila lebih utama. Artinya, hampir separuh dari siswa tidak setuju kalua Pancasila dijadikan ideologi negara. Fenomen ini harus mendapat perhatian serius dari pemerintah agar mereka taat pada aturan perundang-undangan Republik Indonesia.